Comment: Collective Epistemic Emotions and Individualized Learning: A Relational Account. (October 2020) - Sander, David
This comment considers some potential implications of both the appraisal approaches and the framework proposed by Mascolo in regard to a mechanism that is particularly important for development: learning. More specifically, I discuss Mascolo's account of emotion with respect to how appraisal processes can be considered relational, automatic, social, as well as the drivers of learning amplification.